Effect of Physical Activity on Self-Concept: Theoretical Model on the Mediation of Body Image and Physical Self-Concept in Adolescents - Fernández-Bustos, Juan Gregorio; Infantes-Paniagua, Álvaro; Cuevas, Ricardo; Contreras, Onofre Ricardo (Frontiers in Psychology, 2019)
Objective: The aim of this research was to study the mediation of body dissatisfaction, physical self-concept, and body mass index (BMI) on the relationship between physical activity and self-concept in adolescents. Materials and Methods: A sample of 652 Spanish students between 12 and 17 years participated in a cross-sectional study. Physical self-concept and general self-concept were assessed with the Physical Self-Concept Questionnaire (CAF), body dissatisfaction with the Body Shape Questionnaire (BSQ), and physical activity was estimated with the International Physical Activity Questionnaire (IPAQ-SF). BMI was utilized as a measurement of body composition. Structural equation modeling was used to assess the results. Results: The resulting models showed good fit indexes. Physical activity had a positive and indirect effect on self-concept (β = 0.29, p < 0.01) and direct effects on dissatisfaction (β = -0.26, p < 0.01) and physical self-concept (β = 0.20, p < 0.01). BMI had a direct effect on dissatisfaction (β = 0.31, p < 0.01) and on physical self-concept (β = -0.10, p < 0.01) and an indirect effect on general self-concept (β = -0.24, p < 0.01). However, it was only associated with physical activity in males, playing a mediating role between physical activity and body dissatisfaction. Conclusion: Physical activity can help individuals to achieve a positive self-concept and promote psychological well-being in adolescents through the improvement of physical perceptions and body satisfaction. The importance of BMI, body dissatisfaction, and physical self-concept on the configuration of the self-concept are also emphasized. Educational policymakers and Physical Education teachers should implement strategies to promote physical activity in the schools and provide a Quality Physical Education programs to increase physical activity during adolescence.